2021
DOI: 10.3390/cryst11111322
|View full text |Cite
|
Sign up to set email alerts
|

Beryl Reference Materials for In Situ Oxygen Isotope Determination

Abstract: The mineral beryl (Be3Al2(SiO3)6) has the most abundant phase with industrial value for extracting a critical metal—beryllium. Due to multi-stage, fluid-induced growth, individual beryl grains may yield complex geochemical records, revealing variations in the oxygen isotopes of the fluids from which they crystallize. Secondary ion mass spectrometry (SIMS) with high sensitivity and high spatial resolution represents a good tool for in situ isotopic analysis. SIMS oxygen analyses require matrix-matched reference… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 30 publications
0
2
0
Order By: Relevance
“…The homogeneity of oxygen isotope data is an important factor in determining whether a sample can be developed into a specimen reference material [15,35,36]. The homogeneity is accessed by the standard deviation of the measured δ 18 O values.…”
Section: Homogeneitymentioning
confidence: 99%
See 1 more Smart Citation
“…The homogeneity of oxygen isotope data is an important factor in determining whether a sample can be developed into a specimen reference material [15,35,36]. The homogeneity is accessed by the standard deviation of the measured δ 18 O values.…”
Section: Homogeneitymentioning
confidence: 99%
“…The 2SD of the measured oxygen isotope values was 0.57 for sample JAY03-3 and 0.70 for sample JAY02-4. Previous studies indicated that the homogeneity of SIMS oxygen isotope data can be affected by various factors, including instrument stability [16], experimental conditions [22], X-Y axis effect [37], crystal orientation [14,21], and mineral inclusions [35]. However, for olivine crystals, the effect of crystal orientation on homogeneity is negligible (less than 0.5‰).…”
Section: Homogeneitymentioning
confidence: 99%